Respostas

2014-01-15T21:04:19-02:00
Dada a função real f(x)= - 5x + 2k determine k para que zero da função f seja igual - 2.

Para isso vamos atribuir valores para x:
x = - 2
x = - 1
x = 0
x = 1
x = 2

f(x)= - 5x + 2k    ⇒ x = - 2
- 5 (- 2) + 2k = - 2
10 + 2k = - 2
2k = - 2 - 10
2k = - 12
k = - 12 ÷ 2
k = - 6

f(x)= - 5x + 2k    ⇒ x = - 1
- 5 (- 1) + 2k = - 2
5 + 2k = - 2
2k = - 2 - 5
2k = - 7
k = - 7 ÷ 2
k = - 3,5

f(x)= - 5x + 2k    ⇒ x = 0
- 5 * 0 + 2k = - 2
2k = - 2
k = - 2 ÷ 2
k = - 1

f(x)= - 5x + 2k    ⇒ x = 1
- 5 * 1 + 2k = - 2
- 5 + 2k = - 2
2k = - 2 + 5
2k = 3
k = 3 ÷ 2
k = 1,5

f(x)= - 5x + 2k    ⇒ x = 2
- 5 * 2 + 2k = - 2
- 10 + 2k = - 2
2k = - 2 - 10
2k = - 12
k = - 12 ÷ 2
k = - 6